Determinant Factors of Malnutrition in Papuan Children Under Five Years: Structural Equation Model Analysis - Stefanus P. Manongga; Lewi Yutomo (International Journal Labs, 2023)
Malnutrition is a strategic problem in Indonesia, especially in Papua Province, which extends from urban to rural areas. The purpose of this study was to assess the situation of malnutrition and to find structural models of malnutrition in Papuan children in various ecosystem zones in Papua Province. The study was designed in a cross-sectional manner, where the selection of research sites used a multistage sampling procedure with stratification and cluster techniques. Data collection was done through structured interviews, observations, and field measurements. It used the least significant different test and Kruskal Wallis to determine whether there are differences in related variables between ecosystem zones. To test and assess the impact of malnutrition on child development, Structural Equation Modeling-Regression was used with a partial least squares approach. The results showed that the prevalence of undernourished children under five years old, short-nutrition, thin-nutrition, and fat-nutrition was widespread in all ecosystem zones. Malnutrition in the form of short children or stunting (TB/U) can be directly associated with social environmental factors. In order to minimize the problem of stunting in Papua, it is necessary to take steps, including improving the nutritional status and health of mothers and children, especially pregnant women, increasing access to food through a food-based approach, and intensifying program activities for basic health, environmental health, and clean water supply.